2019
DOI: 10.3390/ma12071151
|View full text |Cite
|
Sign up to set email alerts
|

Some of the Latest Active Strengthening Techniques for Masonry Buildings: A Critical Analysis

Abstract: The present paper deals with the retrofitting of unreinforced masonry (URM) buildings, subjected to in-plane shear and out of-plane loading when struck by an earthquake. After an introductive comparison between some of the latest punctual and continuous active retrofitting methods, the authors focused on the two most effective active continuous techniques, the CAM (Active Confinement of Masonry) system and the Φ system, which also improve the box-type behavior of buildings. These two retrofitting systems allow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Being aware of this last statement is of paramount importance for a structural engineer, as one of the main consequences of replacing Figure 6a with Figure 6b is that the value of stress in the straps becomes upper bounded. In other words, there is an upper limit value of the strap stress, which we cannot overcome without damaging the masonry [5]. integral part of the CAM patent, filed in 1999 by Dolce and Marnetto.…”
Section: Some Basic Notions Of the Cam Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Being aware of this last statement is of paramount importance for a structural engineer, as one of the main consequences of replacing Figure 6a with Figure 6b is that the value of stress in the straps becomes upper bounded. In other words, there is an upper limit value of the strap stress, which we cannot overcome without damaging the masonry [5]. integral part of the CAM patent, filed in 1999 by Dolce and Marnetto.…”
Section: Some Basic Notions Of the Cam Systemmentioning
confidence: 99%
“…In [5], we have shown that the nodes of the rectangular CAM net are subjected to pairs of equal and opposite forces in the plane of the wall (Figure 5a). Consequently, they do not receive any in- plane force from the retrofitting system and do not have neither horizontal nor vertical displacements.…”
Section: Some Basic Notions Of the Cam Systemmentioning
confidence: 99%
“…In its original use, where buttresses were structures built against or projecting from a wall, this ancient technique is effective but highly invasive and causes great increases in mass. As a result, with the advent of new technologies, buttresses were gradually abandoned in favor of more recent strengthening techniques, some of which are base isolation, seismic dampers, surface treatments, mortar joint treatments, external steel reinforcement, post-tensioning, mesh reinforcement, reticulatus system, confinement with ring beams, tie bars, and fiber/textile-reinforced mortar [2,[30][31][32]. The straps/strips combined technique recuperates the simple strengthening scheme of the buttress, but minimizing invasiveness and mass increases.…”
Section: Of 35mentioning
confidence: 99%
“…This paper is part of a research project on improving the out-of-plane behavior of masonry walls by combining different strengthening techniques [1][2][3][4]. The key-idea of the combined technique is to exploit friction in order to achieve a mechanical coupling between different strengthening devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation